International organizations : a comparative approach to the management of cooperation, por Jordan, Robert S., Clive Archer, Gregory P. Granger y Kerry Ordes, Londres, 2001, 4ª ed. - Andrade Vergara, Mauricio (Estudios Internacionales, 2006)
-